2013
DOI: 10.1242/dev.088849
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted Igf2r silencing depends on continuous Airn lncRNA expression and is not restricted to a developmental window

Abstract: The imprinted Airn macro long non-coding (lnc) RNA is an established example of a cis-silencing lncRNA. Airn expression is necessary to initiate paternal-specific silencing of the Igf2r gene, which is followed by gain of a somatic DNA methylation imprint on the silent Igf2r promoter. However, the developmental requirements for Airn initiation of Igf2r silencing and the role of Airn or DNA methylation in maintaining stable Igf2r repression have not been investigated. Here, we use inducible systems to control Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 60 publications
1
52
0
Order By: Relevance
“…Also for the imprinted Igf2r/Airn locus, Airn antisense transcription through the Igf2r promoter is required for silencing of Igf2r (5). Studies with an inducible Airn promoter indicate that antisense Airn transcription leads to CpG methylation of the Igf2r promoter, stabilizing the silent state, which can then be maintained in the absence of Airn transcriptional read-through (43). The present findings obtained for an experimental sense-antisense gene pair in undifferentiated and differentiating ESCs, taken together with the above-described findings on physiological gene pairs, clearly demarcate a developmental time window where irreversible silencing is established.…”
Section: Discussionsupporting
confidence: 74%
“…Also for the imprinted Igf2r/Airn locus, Airn antisense transcription through the Igf2r promoter is required for silencing of Igf2r (5). Studies with an inducible Airn promoter indicate that antisense Airn transcription leads to CpG methylation of the Igf2r promoter, stabilizing the silent state, which can then be maintained in the absence of Airn transcriptional read-through (43). The present findings obtained for an experimental sense-antisense gene pair in undifferentiated and differentiating ESCs, taken together with the above-described findings on physiological gene pairs, clearly demarcate a developmental time window where irreversible silencing is established.…”
Section: Discussionsupporting
confidence: 74%
“…It has recently been revealed that the imprinting activity regulated by the lncRNA AIRN is a function of the local act of transcription across the locus and not mediated by the transcript itself (Latos et al 2012;Santoro et al 2013). Prior to this, it was thought to have an activity that was attributed to a functional RNA molecule.…”
Section: In Vivo Lncrna Loss Of Functionmentioning
confidence: 99%
“…These results shed light on two intriguing areas: the role of MRUL in the development of GC MDR and a possible mechanism for MRUL function. lncRNAs can promote the epigenetic silencing of protein-coding genes (43,44). In contrast, lncRNAs can also possess enhancer-like functions to promote expression of neighboring proteincoding genes (40,(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%